Homochiral BINOL-based macrocycles with π-electron-rich, electron-withdrawing or extended spacing units as receptors for C60 - Caricato, Marco; González, Silvia Díez; Arandia Ariño, Idoia; Pasini, Dario (Beilstein Journal of Organic Chemistry, 2014)
The “one-pot” synthesis of several homochiral macrocycles has been achieved by using π-electron-rich, electron-deficient or extended aromatic dicarboxylic acids in combination with an axially-chiral dibenzylic alcohol, derived from enantiomerically-pure BINOL. Two series of cyclic adducts with average molecular D2 and D3 molecular symmetries, respectively, have been isolated in pure forms. Their yields and selectivities deviate substantially from statistical distributions. NMR and CD spectroscopic methods are efficient and functional in order to highlight the variability of shapes of the covalent macrocyclic frameworks. The larger D3 cyclic adducts exhibit recognition properties towards C60 in toluene solutions (up to log Ka = 3.2) with variable stoichiometries and variable intensities of the charge-tranfer band upon complexation.
Keywords: BINOL; C60; carbon nanomaterials; carbon nanostructures; chirality; macrocycles; sensors; supramolecular chemistry

(untitled) - Grave, C.; Schlüter, A. D. (Eur. J. Org. Chem., 2002)

(untitled) - Yamaguchi, Y.; Yoshida, Z.-i. (Chem.–Eur. J., 2003)

(untitled) - Höger, S. (Chem.–Eur. J., 2004)

(untitled) - Zhang, W.; Moore, J. S. (Angew. Chem., Int. Ed., 2006)

(untitled) - Hua, Y.; Ramabhadran, R. O.; Karty, J. A.; Raghavachari, K.; Flood, A. H. (Chem. Commun., 2011)

(untitled) - Pasini, D. (Molecules, 2013)

(untitled) - Droz, A. S.; Diederich, F. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Droz, A. S.; Neidlein, U.; Anderson, S.; Seiler, P.; Diederich, F. (Helv. Chim. Acta, 2001)

The Chemistry of Organolithium Compounds - Yus, M. (Arene-catalyzed lithiation, 2004)

Carbon-Rich Compounds: From Molecules to Materials - Campbell, K.; Tykwinski, R. R. (Chiral Carbon-rich Macrocycles and Cyclophanes, 2006)

(untitled) - Pasini, D.; Ricci, M. (Curr. Org. Synth., 2007)

(untitled) - Ghadiri, M. R.; Granja, J. R.; Buehler, L. K. (Nature, 1994)

(untitled) - Leclair, S.; Baillargeon, P.; Skouta, R.; Gauthier, D.; Zhao, Y.; Dory, Y. L. (Angew. Chem., Int. Ed., 2004)

(untitled) - Fischer, L.; Decossas, M.; Briand, J.-P.; Didierjean, C.; Guichard, G. (Angew. Chem., Int. Ed., 2009)

(untitled) - Sakamoto, J.; Schlüter, A. D. (Eur. J. Org. Chem., 2007)

(untitled) - Gong, B. (Acc. Chem. Res., 2008)

(untitled) - Xu, Y.; Smith, M. D.; Geer, M. F.; Pellechia, P. J.; Brown, J. C.; Wibowo, A. C.; Shimizu, L. S. (J. Am. Chem. Soc., 2010)

(untitled) - Pérez, E. M.; Martin, N. (Org. Biomol. Chem., 2012)

(untitled) - Canevet, D.; Pérez, E. M.; Martin, N. (Angew. Chem., Int. Ed., 2011)

(untitled) - Xia, J.; Bacon, J. W.; Jasti, R. (Chem. Sci., 2012)

(untitled) - Tashiro, K.; Aida, T.; Zheng, J.-Y.; Kinbara, K.; Saigo, K.; Sakamoto, S.; Yamaguchi, K. (J. Am. Chem. Soc., 1999)

(untitled) - Shoji, Y.; Tashiro, K.; Aida, T. (J. Am. Chem. Soc., 2006)

(untitled) - Liu, S.-Q.; Wang, D.-X.; Zheng, Q.-Y.; Wang, M.-X. (Chem. Commun., 2007)

(untitled) - Canevet, D.; Gallego, M.; Isla, H.; de Juan, A.; Pérez, E. M.; Martin, N. (J. Am. Chem. Soc., 2011)

(untitled) - Cao, R., Jr; Isla, H.; Cao, R.; Pérez, E. M.; Martin, N. (Chem. Sci., 2011)

(untitled) - Moletti, A.; Coluccini, C.; Pasini, D.; Taglietti, A. (Dalton Trans., 2007)

(untitled) - Coluccini, C.; Castelluccio, A.; Pasini, D. (J. Org. Chem., 2008)

(untitled) - Coluccini, C.; Dondi, D.; Caricato, M.; Taglietti, A.; Boiocchi, M.; Pasini, D. (Org. Biomol. Chem., 2010)

(untitled) - Coluccini, C.; Mazzanti, A.; Pasini, D. (Org. Biomol. Chem., 2010)

(untitled) - Caricato, M.; Coluccini, C.; Dondi, D.; Vander Griend, D. A.; Pasini, D. (Org. Biomol. Chem., 2010)

(untitled) - Colombo, S.; Coluccini, C.; Caricato, M.; Gargiulli, C.; Gattuso, G.; Pasini, D. (Tetrahedron, 2010)

(untitled) - Caricato, M.; Olmo, A.; Gargiulli, C.; Gattuso, G.; Pasini, D. (Tetrahedron, 2012)

(untitled) - Boiocchi, M.; Bonizzoni, M.; Moletti, A.; Pasini, D.; Taglietti, A. (New J. Chem., 2007)

(untitled) - Bencini, A.; Coluccini, C.; Garau, A.; Giorgi, C.; Lippolis, V.; Messori, L.; Pasini, D.; Puccioni, S. (Chem. Commun., 2012)

(untitled) - Caricato, M.; Leza, N. J.; Gargiulli, C.; Gattuso, G.; Dondi, D.; Pasini, D. (Beilstein J. Org. Chem., 2012)

(untitled) - Caricato, M.; Coluccini, C.; Vander Griend, D. A.; Forni, A.; Pasini, D. (New J. Chem., 2013)

(untitled) - Caricato, M.; Leza, N. J.; Roy, K.; Dondi, D.; Gattuso, G.; Shimizu, L. S.; Vander Griend, D. A.; Pasini, D. (Eur. J. Org. Chem., 2013)

(untitled) - Caricato, M.; Sharma, A. K.; Coluccini, C.; Pasini, D. (Nanoscale, 2014)

(untitled) - Asakawa, M.; Ashton, P. R.; Boyd, S. E.; Brown, C. L.; Menzer, S.; Pasini, D.; Stoddart, J. F.; Tolley, M. S.; White, A. J. P.; Williams, D. J.; Wyatt, P. G. (Chem.–Eur. J., 1997)

(untitled) - Stock, H. T.; Kellogg, R. M. (J. Org. Chem., 1996)

(untitled) - Rosini, C.; Superchi, S.; Peerlings, H. W. I.; Meijer, E. W. (Eur. J. Org. Chem., 2000)

(untitled) - Baudry, Y.; Bollot, G.; Gorteau, V.; Litvinchuk, S.; Mareda, J.; Nishihara, M.; Pasini, D.; Perret, F.; Ronan, D.; Sakai, N.; Shah, M. R.; Som, A.; et al. (Adv. Funct. Mater., 2006)

(untitled) - Ercolani, G. (J. Am. Chem. Soc., 2003)

(untitled) - Hamacek, J.; Piguet, C. (J. Phys. Chem. B, 2006)

(untitled) - Moore, S.; Stupp, S. I. (Macromolecules, 1990)